Physical and Psychological Health Challenges Among Dental Practitioners During the COVID-19 Pandemic: A Study from Chattogram City (Bangladesh Journal of Medical Education, 2026)
Background: Dental practitioners were among the most vulnerable professionals throughout the COVID-19 pandemic due to their exposure to aerosols and close patient contact. This study assessed the physical and psychological health challenges faced by dental practitioners in Chattogram City. Methods: This cross-sectional study was conducted amongst 96 dental practitioners of Chattogram city, from May 2023 to April 2024. Data were collected using a structured, pretested online questionnaire covering demographic details, physical symptoms, psychological impacts, and infection-control practices in dental clinics. Descriptive statistics and Chi-square/ Fisher’s exact tests were applied as appropriate (p